Association Between Chemotherapy and Survival in T1 Colon Cancer With Lymph Node Metastasis: A Propensity-Score Matched Analysis - Yan, Wangxin; Zhou, Huizhen; Shi, Si; Lin, Jixu; Lin, Qiangkang (Frontiers in Oncology, 2021)
Purpose: To comprehensively examine the efficacy of chemotherapy in T1 colon cancer patients with lymph node metastasis. Methods: The differences of the categorical variables in colon cancer patients according to the lymph node status were assessed by Pearson’s chi-square test. The Kaplan-Meier method was used to estimate the CSS with the log-rank test. Cox proportional hazards models were built, multivariate Cox regression analyses were performed with hazard ratio (HR) and 95% confidence interval (CI) to identify the potential independent prognostic factors. Propensity score matching was done to adjust for treatment bias due to measured confounders Results: Younger age (52.2% VS. 43.0% for ≤ 65 years old, p < 0.001), female (50.3% VS. 46.8% for female, p < 0.001), more lymph node harvested (68.1% VS. 46.6% for ≥12 lymph nodes harvested, p < 0.001), black race (13.6% VS. 12.0% for black race, p < 0.001) and higher tumor grade (14.2% VS. 5.6% for grade III/IV, p < 0.001) were more prone to be diagnosed with lymph node involvement. The receipt of adjuvant chemotherapy following radical surgery would significantly decrease the risk of colon cancer specific mortality by 33.9% compared with those without adjuvant chemotherapy after propensity score matching (HR = 0.661, 95%CI = 0.476-0.917, p = 0.013). Conclusions: Younger age, female, more lymph node harvested, black race and higher tumor grade were more prone to be diagnosed with lymph node involvement. The receipt of adjuvant chemotherapy following radical surgery would significantly decrease the risk of colon cancer-specific mortality by 33.9% compared with those without adjuvant chemotherapy in T1 colon cancer with lymph node involvement.